2018
DOI: 10.5935/abc.20180139
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Quantitative Aortographic Assessment of Aortic Regurgitation by Videodensitometry in the Guidance of Transcatheter Aortic Valve Implantation

Abstract: BackgroundBalloon post-dilatation (BPD) is often needed for optimizing transcatheter heart valve (THV) implantation, since paravalvular leak (PVL) after transcatheter aortic valve implantation is associated with poor outcome and mortality. Quantitative assessment of PVL severity before and after BPD is mandatory to properly assess PVL, thus improving implantation results and outcomes.ObjectiveTo investigate a quantitative angiographic assessment of aortic regurgitation (AR) by videodensitometry before and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, the long-term vital prognostic value of a threshold of 17% in AR has been reported [12]. The improvement in AR following post-balloon dilatation has also been assessed with this technique, and its impact on long-term prognosis has been demonstrated [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the long-term vital prognostic value of a threshold of 17% in AR has been reported [12]. The improvement in AR following post-balloon dilatation has also been assessed with this technique, and its impact on long-term prognosis has been demonstrated [13].…”
Section: Introductionmentioning
confidence: 99%
“…Postimplantation balloon dilatation improvement in AR has also been quantitatively documented in a series of 61 patients [15]. Importantly, video densitometry-derived AR has proven to be a predictor of long-term prognosis after TAVR, with a >17 % threshold of AR identifying those at risk of long-term mortality [10,15]. The results of quantitative analyses of Evolut Pro, Evolut R, CoreValve (Medtronic, Dublin, Ireland), and Acurate Neo (Boston Scientific, Massachusetts, USA) were retrieved from a published pooled database [8].…”
Section: Methodsmentioning
confidence: 91%
“…It is similar to angiography and transesophageal echocardiography-guided procedures [19]. Based on the previous validation [8,13,14], quantitative aortographic assessment of AR has been shown to be an objective, accurate, and reproducible tool for assessment of AR following TAVR, and has the potential to facilitate timely decision-making to correct the AR with balloon post-dilatation, when additional corrective maneuvers are mandatory from a functional and prognostic perspective [15]. Conversely the online, objective and quantitative assessment also allows for the decision making to avert an unnecessary post-dilatation of the THVs that always entails the risk of a potential, manifest or silent, neurologic event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that left atrium (LA) size and function are important predictors of cardiovascular events in several clinical settings and can be involved in the progression to heart failure. 51-52 In another interesting article published in Rev Port Cardiol, Fontes-Carvalho et al 53 evaluated in 94 patients after AMI the role of different indices of LA function (assessed by speckle tracking) as determinants of exercise capacity by cardiopulmonary exercise testing. They found a significant correlation between exercise capacity and LA conduit function, but not with contractile function.…”
Section: Cardiac Function Exercise Capacity and Heart Failurementioning
confidence: 99%